Pemisahan Emas Pada PC Mainboard Komputer : Pengaruh Rasio Sampel : HNO3 Dan Jenis Presipitan - Esti Rahmat Tini; Yusnimar Yusnimar; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Gold (Au) has been used widely in the electronics and telecommunications industries. In the Printed Circuit (PC mainboard, the former metal there are approximately 80-1000 ppm Au. In this study Au has been separated from PC Mainboard with treatment variation ratio of the amount of samples and HNO3 (1: 3; 1: 6; and 1: 9 w/v) and the type of precipitants (NaHSO3 and H2C2O4). Gold content was determined by Atomic Absorption Spectrophotometry. For 5 grams PC mainboard sample with a size of 1-10 mm was leaching with HNO 3 at T=70°C for 1 hour, the precipitate formed is separated from the filtrate. Then, the precipitate obtained was leaching with aqua regia at T=70°C for 30 minutes, the precipitate dissolved and further it diluted with aqua DM until it is volume 50 mL. Later, concentration Au is analyzed by AAS and Au are deposited using a precipitant H2C2O4 and NaHSO3. According to the result, content of Au in the PC mainboard is 300 ppm. For 5 grams amount of sample is obtained maximum weight of 2.14 grams Au deposition using H2C2O4 as a precipitant.Keywords: Au, leaching, PC Mainboard, precipitant.